Bioethanol Production from Iles-Iles (Amorphopallus campanulatus) Flour by Fermentation using Zymomonas mobilis - Kusmiyati, Kusmiyati; Hadiyanto, H; Kusumadewi, Indah (Center of Biomass & Renewable Energy, Diponegoro University, 2016)
Due to the depletion of fossil oil sources, Indonesia attempts to search new source of bioenergy including bioethanol. One of this sources is Iles-iles tubers (Amorphophallus campanulatus), which is abundantly available in Java Indonesia. The carbohydrate content in Iles-Iles tuber flour was 77% and it can be converted to ethanol by three consecutive steps methods consist of liquefaction-saccharification using α and β-amylase, respectively and then followed by fermentation by using Z. mobilis. The objective of this research was to convert the Iles-iles flour to bioethanol by fermentation process with Z.mobilis. The ethanol production process was studied at various starch concentration 15-30% g/L, Z. mobilis concentration (10-40%) and pH fermentation of (4-6). The result showed that the yield of bioethanol (10.33%) was the highest at 25% starch concentration and 25% of Z.mobilis concentration. The optimum conditions was found at 4.5, 30°C, 10%, 120 h for pH, temperature, Z. mobilis concentration and fermentation time, respectively at which ACT tuber flour produced a maximum ethanol of 10.33 % v/v.Article History: Received November 12nd 2015; Received in revised form January 25th 2016; Accepted January 29th 2016; Available online How to Cite This Article: Kusmiyati , Hadiyanto,H and Kusumadewi, I (2016). Bioethanol Production from Iles-Iles (Amorphopallus campanulatus) Flour by Fermentation using Zymomonas mobilis. Int. Journal of Renewable Energy Development, 9(1), 9-14 http://dx.doi.org/10.14710/ijred.5.1.9-14